PVN-centered multi-omics and single-cell analyses suggest shared inflammatory and immune features in acute myocardial infarction-associated ventricular arrhythmia and atrial fibrillation - Wenlong Wang; Wenbo Zhao; Yuran Chen; Xin Wang; Chunrui Ji; Jingmei Sun; Yu Bai; Yuhang Yang; Xiufen Qu (Frontiers in Cardiovascular Medicine, 2026)
Objective Acute myocardial infarction (AMI) increases the risk of arrhythmias, particularly ventricular arrhythmias (VA), and atrial fibrillation (AF) is also common after AMI. The paraventricular nucleus (PVN) is a key regulator of sympathetic outflow. This study used a PVN-centered strategy to investigate molecular changes after AMI, prioritize candidate molecules associated with VA, and assess whether related inflammatory and immune features are also present in AF cohorts. Methods An AMI model was established in C57BL/6 mice, and PVN tissues were collected at 48 h and 7 d for transcriptomic and metabolomic profiling. Electrocardiogram (ECG) telemetry, histological assessment and serum markers were used to evaluate infarct injury and arrhythmia burden, and immunofluorescence was used to assess glial responses and nuclear factor- κ B (NF- κ B) activation in the PVN. Two-sample Mendelian randomization (MR), summary-data-based Mendelian randomization (SMR) and colocalization analyses were performed to prioritize candidate molecules associated with VA. External analyses were conducted in AF cohorts (GSE41177 and GSE261170). Functional support was evaluated by bilirubin intervention in vivo and Il12rb1 knockdown in a BV2 hypoxia/reoxygenation (H/R) model. Results AMI increased premature ventricular contractions and ventricular tachycardia burden, together with elevated cardiac troponin I and increased ionized calcium-binding adaptor molecule 1 (Iba1), glial fibrillary acidic protein (GFAP) and phosphorylated NF- κ B p65 (p-p65) signals in the PVN. MR suggested an inverse association between direct bilirubin and VA risk, and bilirubin treatment reduced arrhythmia burden and PVN inflammatory activation. MR/SMR analyses prioritized DGKQ, BLM, ABCA3 and IL12RB1 as candidate genes associated with VA. In AF cohorts, these genes were differentially expressed, and pathway, immune infiltration and single-cell analyses suggested inflammatory, hypoxic and immune remodeling in cardiac tissue. In vitro , Il12rb1 knockdown reduced p-p65, interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) under H/R conditions. Conclusion These findings support a PVN-centered framework in which inflammatory and immune processes may contribute to post-AMI arrhythmia vulnerability. Direct bilirubin and DGKQ, BLM, ABCA3 and IL12RB1 may represent candidate molecules for further investigation.